Vorinostat in refractory soft tissue sarcomas: results of a multi-centre phase II trial of the German Soft Tissue Sarcoma and Bone Tumour Working Group (AIO) - Schmitt, Thomas; Kasper, Bernd; Hüsing, Johannes; Hajda, Jacek; Ottawa, Gregor; Mechtersheimer, Gunhild; Mikus, Gerd; Burhenne, Jürgen; Lehmann, Lorenz; Heilig, Christoph E.; Ho, Anthony Dick; Egerer, Gerlinde (European journal of cancer, 2016)
Introduction: New treatment options for patients with metastatic Soft Tissue Sarcoma are urgently needed. Preclinical studies suggested activity of vorinostat, a histone deacetylase inhibitor. Methods: A multi-centre, open-label, non-randomised phase II trial to investigate the efficacy and safety of vorinostat in patients with locally advanced or metastatic Soft Tissue Sarcoma failing 1st-line anthracycline-based chemotherapy was initiated. Patients were treated with vorinostat 400 mg po qd for 28 d followed by a treatment-free period of 7 d, representing a treatment cycle of 5 weeks. Restaging was performed every three cycles or at clinical progression. Results: Between 06/10 and 09/13, 40 Soft Tissue Sarcoma patients were treated with vorinostat at seven participating centres. Patients had received 1 (n = 8, 20%), 2 (n = 10, 25%) or ≥3 (n = 22, 55%) previous lines of chemotherapy. Best response after three cycles of treatment was stable disease (n = 9, 23%). Median progression-free survival and overall survival were 3.2 and 12.3 months, respectively. Six patients showed long-lasting disease stabilisation for up to ten cycles. Statistical analyses failed to identify baseline predictive markers in this subgroup. Major toxicities (grade ≥III) included haematological toxicity (n = 6, 15%) gastrointestinal disorders (n = 5, 13%), fatigue (n = 4, 10%), musculoskeletal pain (n = 4, 10%), and pneumonia (n = 2, 5%). Conclusion: In a heavily pre-treated patient population, objective response to vorinostat was low. However, a small subgroup of patients had long-lasting disease stabilisation. Further studies aiming to identify predictive markers for treatment response as well as exploration of combination regimens are warranted. Trial registration: NCT00918489 (ClinicalTrials.gov) EudraCT-number: 2008-008513-19